2012
DOI: 10.5665/sleep.1832
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Polysomnographic Predictors of the Natural History of Poor Sleep in the General Population

Abstract: Poor sleep appears to be primarily a symptom of physical and mental health conditions, whereas the persistence of poor sleep is associated with psychologic distress. Importantly, sleep apnea appears to be associated with incident poor sleep but not with chronic insomnia. Finally, this study suggests that objective short sleep duration in poor sleepers is a biologic marker of genetic predisposition to chronic insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
100
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 43 publications
9
100
2
Order By: Relevance
“…These findings further support that objective short sleep duration is a biological marker that predicts both the severity 2 and the natural course of the disorder. 5,6 We agree with Dr Kawada 1 that the use of polysomnographic measures provides strong validity for the findings reported in our study and that future longitudinal studies using longer and multiple followups should further examine the relationship among the natural history of insomnia, objective sleep duration, and cardiovascular risk.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…These findings further support that objective short sleep duration is a biological marker that predicts both the severity 2 and the natural course of the disorder. 5,6 We agree with Dr Kawada 1 that the use of polysomnographic measures provides strong validity for the findings reported in our study and that future longitudinal studies using longer and multiple followups should further examine the relationship among the natural history of insomnia, objective sleep duration, and cardiovascular risk.…”
supporting
confidence: 87%
“…In a previous study, we showed that ≈17% of poor sleepers become chronic insomniacs and that objective short sleep duration is a predictor of the development of full-blown chronic insomnia among poor sleepers 5 ; thus, it is unlikely that poor sleepers with normal sleep duration will become over time chronic insomniacs with short sleep duration. These findings further support that objective short sleep duration is a biological marker that predicts both the severity 2 and the natural course of the disorder.…”
mentioning
confidence: 92%
“…These associations persisted even after controlling for the potentially confounding effects of comorbid sleep apnea, which is known to be strongly linked with hypertension [16] and which is known to overlap to a substantial degree with insomnia [2,25,26]. The association of insomnia with markers of physiologic hyperarousal [3][4][5][6] and the previously reported finding that hypertension is not associated with incident insomnia risk [27] suggest forward causality as the basis for the potential relationship between insomnia with short sleep time and hypertension. Given that short sleep time has been previously reported to be linked with hypertension [17], and that no relationship was found between insomnia symptoms and hypertension when not considering sleep duration in this study, it may be hypothesized that the presence of short sleep time alone is responsible for the significant hypertension associations in the insomnia-short sleep time subgroup.…”
Section: Insomnia and Hypertensionmentioning
confidence: 49%
“…In our design, we consider participants' sociodemographic and clinical features as they might influence PSG parameters [46,47]. We expected that PSG parameters would distinguish FMS patients from controls.…”
Section: Introductionmentioning
confidence: 99%